2020
DOI: 10.1002/aic.17109
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of ellipsoidal granular particles in shear flow

Abstract: The diffusion of nonspherical particles has not been well understood due to the complexity of their contact mechanics and self‐organization of their orientations. We perform discrete element method simulations of monodisperse ellipsoids in a shear flow with Lees‐Edwards boundary conditions to quantify the relation between the diffusion coefficient and the flow parameters. The results indicate that the particle aspect ratio strongly affects the diffusion coefficient by influencing the particle orientation and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…In fact, monodisperse assemblies of non-spherical particles are suitable to isolate diffusion from other mechanisms. Recently, R. Cai et al 23 numerically examined self-diffusion in a system of ellipsoids, using Lees-Edwards boundary conditions, and varying the particle aspect ratio systematically. They proposed a generalized scaling law for the diffusivity in the direction perpendicular to the flow in terms of an effective particle size d eff , the aspect ratio x and the solid fraction f, namely, D B w (f, x)_ gd eff 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, monodisperse assemblies of non-spherical particles are suitable to isolate diffusion from other mechanisms. Recently, R. Cai et al 23 numerically examined self-diffusion in a system of ellipsoids, using Lees-Edwards boundary conditions, and varying the particle aspect ratio systematically. They proposed a generalized scaling law for the diffusivity in the direction perpendicular to the flow in terms of an effective particle size d eff , the aspect ratio x and the solid fraction f, namely, D B w (f, x)_ gd eff 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The modelling results showed that particle aspect ratio is closely associated to particle alignments and direction at the continuous shear rate and ref. 77 . later confirmed the findings of this work.…”
Section: Introductionmentioning
confidence: 99%